M12 A randomised, controlled trial of a 12 week multi-modal exercise intervention in huntington's disease. (13th September 2016) - Quinn, Lori; Hamana, Katy; Kelson, Mark; Dawes, Helen; Collett, Jonathan; Townson, Julia; Roos, Raymund; Plas, Anne van der; Reilmann, Ralf; Frich, Jan; Rickards, Hugh; Rosser, Anne; et al.
Abstract : Background: This study aimed to evaluate the feasibility and benefit of a structured exercise intervention in people with Huntington's disease (HD). Methods: This study was conducted at 6 sites, and participants were randomised into either exercise or control (usual care) groups, and were assessed at baseline, 13 and 26 weeks. The intervention was 12 weeks, three times per week progressive exercise program, including aerobic (stationary cycling) and upper and lower body strengthening exercise with tapered 1:1 support for 20 of 36 sessions. The trial was registered (Current Controlled Trials ISRCTN11392629 ). Results: 314 adults were assessed for eligibility: 248 did not meet inclusion criteria, 34 declined, and 32 were recruited and randomised. Three individuals in the intervention group were withdrawn within the first month due to concomitant medical conditions, resulting in 14 participants in intervention and 15 in control groups. There were two AEs in the intervention group, both related to previous medical conditions, and there were two SAEs, both in the control group. The intervention group had statistically significantly better fitness (predicted VO2 max difference: 493.3 ml.min-1, 95% CI: [97.1, 887.6]), lower UHDRS mMS (difference 2.9 points, 95% [−5.42, −0.32]) and lower weight at Week 13 (difference 2.25 kg, 95% CI: [−4.47, −0.03]). Conclusions: This study demonstrates that a short-term exercise intervention is safe and feasible. Individuals with HD may benefit from structured exercise, and intensity, monitoring and support may be key factors in optimising response. Larger scale trials are now required to fully elucidate the extended clinical potential of exercise in HD. This trial was funded by The Jacques and Gloria Gossweiler Foundation.